Simplifying the complex : a guide to transition and activation planning for healthcare construction projects /: a guide to transition and activation planning for healthcare construction projects. (2020) - Guzman, Kelly; Agner, Jeff; Aguilera, Lynn; Stevenson, Kathy
No abstract available